Sex disparity in adult asthma—A potential immunomodulatory role of let‐7 family microRNAs - Carina Malmhäll; Jenny Calvén; Julie Weidner; Kristina Johansson; Patricia Ramos‐Ramírez; Emma Boberg; Linda Ekerljung; Roxana Mincheva; Bright Nwaru; Hannu Kankaanranta; Henric Olsson; Christopher McCrae; et al. (Clinical and Translational Allergy)
Abstract Background Sex differences have been reported in the incidence, prevalence and severity of asthma. Previous findings from animal models have revealed sex‐related differences in inflammatory pathways that may contribute to asthma pathogenesis, but human studies are limited. Methods Airway and blood samples (n = 55 and n = 85 respectively) were collected from adult females and males with asthma and healthy subjects. Type 2 innate lymphoid cells (ILC2s), T helper (Th)2 cells and their expression of IL‐33R/ST2 (ST2L) were evaluated by flow cytometry. IL‐13, thymic stromal lymphopoietin (TSLP), IL‐33 and soluble IL‐33R/ST2 (sST2) were measured by ELISA. Let‐7 miRNA expression in bronchial biopsies was determined by qPCR. Results Females with asthma reported more exacerbations and had a higher number of airway eosinophils compared with males with asthma. Bronchial biopsy expression of Let‐7f, Let‐7g and miR‐98 tended to be higher in males with asthma compared with females and inversely correlated with asthma exacerbations. In contrast, increased levels of IL‐13, TSLP and sST2 were found in females with asthma compared with males. Conclusion Our study demonstrates different inflammatory signatures between males and females with asthma. Let‐7 miRNAs act as immune modulators by inhibiting the production of IL‐13 and may be an important factor explaining the sex disparity seen in asthma.